2015
DOI: 10.1007/s40071-015-0106-x
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic pyrethroids (Type II) and freshwater fish culture: Perils and mitigations

Abstract: As a new class of agricultural insecticides, synthetic pyrethroids are widely used to control insect pests. Synthetic pyrethroids have been shown to enter the aquatic environment from agricultural runoff or drift from aerial and ground-based spraying applications posing threat to fishes which are less tolerant to pesticides through direct exposure. These insecticides interfere with the sodium channel of the nervous system resulting in prolonged sodium tail current. Widespread application of these chemicals has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 173 publications
(202 reference statements)
3
16
0
1
Order By: Relevance
“…It was possible to observe that, even in a concentration 2.3 times higher than the concentration suggested as limit in the acute toxicity tests on fish, the mortality was less than 15% (S1A Fig). This toxicity is lower than that observed with pyrethroids for fish and other aquatic organisms, for example [87].…”
Section: Discussionmentioning
confidence: 76%
“…It was possible to observe that, even in a concentration 2.3 times higher than the concentration suggested as limit in the acute toxicity tests on fish, the mortality was less than 15% (S1A Fig). This toxicity is lower than that observed with pyrethroids for fish and other aquatic organisms, for example [87].…”
Section: Discussionmentioning
confidence: 76%
“…Water covers about 70% of the earth, and happens to be the most essential natural resources [15]. Despite this awareness of the essentiality of water, humans have ignored its importance by polluting it [16]. The advancement in industrialization has coincided with the problem of aquatic pollution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the developing embryos of the non-target animals are much more sensitive to toxic insults as compared to the adults' due to their partial metabolic incapability for detoxification and the easily distortable intricate developmental processes (tissues and organs differentiation) they are rapidly passing through. It is worth mentioning here that the type II pyrethroid insecticides are highly toxic to fish adults (Prusty et al, 2015); whereas CN has already been reported to be toxic for the developing zebrafish embryos (Shi et al, 2011). Moreover, the combined embryo toxic effects of CN and permethrin in zebrafish have also been reported (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 81%